(untitled) (Albayan Scientific Journal, 2023)
The study dealt with the elements of tourism development in the city of bardi This is due to the importance of tourism as an important economic sector that can bring hard currency and provide new job opportunities. This presentation also contributes to how to exploit these components in the development of the tourism industry, based on its characteristics and characteristics. Keywords: Ingredients, bardi, Tourism Geography.